Enacting Blue Economy in Indonesia: Addressing Climate Change within Global Legal Framework - Sabatira, Febryani; Davey, Orima; Putri, Ria Wierma (Journal of Law and Policy Transformation, 2023)
The World Bank has launched a maritime economic-environmental strategy referred to as the blue economy. This strategic initiative places a strong emphasis on sustainability in marine economic endeavors, aiming to generate both economic and social benefits while protecting the lasting integrity of marine ecosystems amidst the challenges of climate change. The core objective of the blue economy is to notably improve human welfare and social equity while simultaneously reducing environmental risks and ecological scarcities. The relevance of the blue economy concept is especially pronounced in countries with extensive water bodies, such as Indonesia. As an archipelagic state, Indonesia holds significant promise for the development and utilization of marine resources. Leveraging this economic potential holds the potential to create new job opportunities, enhance food security, and support the sustainability of global marine ecosystems. In this regard, adopting a blue economy strategy emerges as a compelling approach to achieve these objectives, especially given that a significant portion of Indonesia's population relies on traditional fishing for their livelihoods. The upcoming research aims to explore two fundamental aspects: firstly, the regulatory framework of the blue economy in relation to climate change, adhering to international legal standards; and secondly, the practical implementation of the blue economy in addressing climate change challenges specific to Indonesia. This research employs a normative research methodology, characterized by a problem-solving approach structured across a series of defined stages.